Decision Support System for the Selection of Outstanding Students Using the MAUT Method - Ridha Maya Faza Lubis; Mesran Mesran; Nopri Prayoga; Sindi Apri Nesya; Agus Perdana Windarto; Rizkah Fadillah; Setiawansyah Setiawansyah (ADA Research Center, 2025)
The selection of outstanding students is one of the efforts of universities in giving awards to students who have the best academic and non-academic achievements. The problem that often occurs in the selection process of outstanding students is that assessments still focus on one main criterion, namely the Cumulative Achievement Index (GPA), so that the results obtained are less objective and do not reflect the overall ability of students. Therefore, this study aims to design and implement a Decision Support System (DSS) in the selection of outstanding students by considering various assessment criteria. The method used in this study is Multi Attribute Utility Theory (MAUT), which is one of the multicriteria decision-making methods. The criteria used in the study included GPA, foreign language skills, organizational activeness, number of scientific papers, and history of taking remedial exams. The MAUT method is used to calculate the utility value of each alternative based on the weight and value of each criterion, so that student rankings are obtained objectively. The results of the study show that the implementation of DSS using the MAUT method can help the selection process of outstanding students in a more systematic and transparent manner. Based on the calculation results, the best alternative was obtained in alternative A5 on behalf of